Nursing Consultation Before kidney transplantation: an activity related to the self-care - Proença, Maria Conceição da Costa; Vicari, Alessandra Rosa; Gonçalves , Débora Hexsel (Brazilian Journal of Transplantation, 2009)
Nursing consultation is a resource used by nurses aiming the patient’s care, the family, groups or communities as to priorize the independency and autonomy of the individual regarding educative and preventive aspects. The assistance planning, risk factors, and nursing diagnosis detection added to interventions are all included in order to achieve the results. The purpose of this work is to describe the experience on renal pre-transplantation nursing consultation as an educative activity for patients candidate to a waiting list. Computerized physical as- sessment and nursing evolution models are used, which are elaborated according to Weed (subjective, objective, analysis or interpretation and plan or behavior), along with Wanda Horta’s theory, priorizing basic human needs. This system (referred to as “Aplicativos de Gestão Hospitalar (AGH)”, has been elaborated by professionals according to their areas of activity, as well as by the HCPA system analysis team. The experience of the pre-transplantation nursing consultation according to this model and theory provided the nurses the necessary in- formation as to the patient’s ability to perform the self-care, as well as the possibility to develop an individual care planning, taking into account the patient, his family, group or community’s experience and knowledge. The same experience allowed to refer to other medical specialties such as: nutrition, odontology, gynecology and social working. In short, the pre-transplantation consultation provides the patient and family members the possibility of having a meaningful support from the care team, once they will be able to clarify any doubts and to establish an important dialogue with the caretakers.